Representasi Narasi Distopia Psikologis dan Sosial dalam Novel 24 Jam Bersama Gaspar Karya Sabda Armandio - Nurul Bayyinah; I G.A.A. Mas Triadnyani; Isnan Waluyo (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
This article aims to describe the forms of dystopian narrative in the novel 24 Hours with Gaspar by Sabda Armandio. Unlike classical dystopian works that commonly portray futuristic societies, advanced technologies, authoritarian governments, or post-apocalyptic settings, the dystopian elements in this novel emerge in a more subtle and realistic manner through social conditions that are closely connected to everyday human experiences. This study employs a qualitative descriptive method with a literary text analysis approach. The data consist of narrative excerpts, dialogues, and inner monologues that reflect various dimensions of dystopia, including spiritual, existential, social, and moral aspects. The analysis reveals that dystopia in the novel is manifested through the loss of the sacredness of God, the normalization of death and violence, the erosion of hope and future orientation, the breakdown of family relationships, and the dehumanization of individual identity. Furthermore, the novel portrays moral corruption, institutional decay, social alienation, and the absurdity of justice as systemic conditions shaping human life. These dystopian representations illustrate how modern society experiences a gradual degradation of values and meaning. Overall, the novel offers a profound critique of contemporary humanity and serves as a reflective commentary on the social, moral, and existential crises of the modern world.